Panicle Length and Weight Performance of F3 Population from Local and Introduction Hybridization of Rice Varieties - ANGELITA PUJI LESTARI; . SUWARNO; . TRIKOESOEMANINGTYAS; DIDY SOPANDIE; HAJRIAL ASWIDINNOOR (HAYATI Journal of Biosciences, 2015)
Plant breeding program consists of establishment of the population, selection, and evaluation. The study aimed to observe the variability of yield components, the heritability, and the distribution of the yield component characters in the F3 populations. The experiment was conducted at Muara Experimental Farm Bogor, from April to August 2012 on Latosol soil. The F3 populations derived from crosses of Bintang Ladang x US2, Gampai x IR77674, and Progol x Asahan and their parental were used as plant materials. Twenty one-day-old seedlings from each population were planted in plots of 2 x 12 m, with planting space of 20 x 20 cm and 3-5 seedlings per hole. Panicle length and weight were observed on 300 randomly selected plant samples from each population. The results showed that there was a variation of agronomic characters among genotypes. The heritability of characters, the panicle length and weight was low to high. Panicle length and weight were controlled by many genes with additive gene action in the Gampai x IR77674 derived population, while panicle weight was controlled by few genes with complementary epistatic additive gene action in both Bintang Ladang x US2 and Progol x Asahan derived populations. The more genes controlling a character, the more distribution classes formed and the greater variance among genotypes.